Effects of salinity stress on morphological structure, physiology, and mRNA expression in different wheat (Triticum aestivum L.) cultivars - Sun, Xiaohui; Tan, Yuliu; Zhang, Yumei; Guo, Weiwei; Li, Ximei; Golub, Nataliia; Zhang, Lili; Wang, Huifang (Frontiers in Genetics, 2025)
Salinity is a major abiotic stress that threatens crop yield and food supply in saline soil areas. Wheat (Triticum aestivum L.) is the most important cereal crop in arid and semiarid land areas, which are often adversely affected by soil salinity. Hence, creating salt tolerance wheat is of great value for utilizing saline soils. In this study, two wheat cultivars QingMai 6 (QM6, salt-tolerant) and Chinese Spring (CS, salt-sensitive) were subjected to salinity stress. Morphological analysis showed that the seedlings of QM6 grew better than CS under salt stress conditions, especially in roots. Electron microscopic studies revealed that salinity stress caused significantly more root hairs and less effect on normal chloroplast structure in QM6 than these in CS. Moreover, QM6 showed a higher photosynthetic activity under salt stress conditions compared to CS. Further investigation showed the salt-tolerant phenotypes of QM6 were accompanied by decreases of reactive oxygen species (ROS) content, and lower antioxidant enzyme activities after salt treatment compared with CS. Additionally, qRT-PCR analyses revealed that the expression level of ROS-scavenging genes (TaSOD6, TaCAT1/5/6, TaPOD7, TaP5CS1) and stress-responsive genes (TaDREB3, TaWRKY19, TaERF5a, TaLTP1, TaTIP2) displayed more transcripts in QM6 than CS. These results provide insight into the mechanisms underlying salt tolerance in wheat, and could be potentially used to develop salt tolerant wheat varieties.